Mapeamento das áreas mecanizáveis da bacia hidrográfica Apodi-Mossoró aplicando avaliação multicriterial - Carlos Júnior, Antônio Aldísio (Universidade Federal Rural do Semi-Árido, 2016)
The land use with mechanized practices by introducing agricultural machinery and implements consists of a technology that maximizes the profitability of crops. However, the introduction of this technology in not conducive areas without proper conservation actions results in intensification of land degradation. In this context, the aim of this study was to map and quantify areas of Apodi-Mossoró watershed about the degree of impediment to the use of agricultural machinery and implements employed in tillage operations. Therefore, it was considered as criteria the slope information, stoniness, depth, drainage and texture of the soil, which were ranked in sub-criteria that defined impediment classes as null, slight, moderate, strong and very strong. The methodology used was the multi-criteria evaluation integrated to the geographic information system through the applying of normalization techniques, weighting and combination of the criteria. The normalization was performed with allowance of fuzzy logic for quantitative criteria (slope, stoniness and depth) and the participatory technique for qualitative criteria (drainage and texture). The weighting to measure the importance of each criterion was obtained by the AHP - Analytic Hierarchy Process and, for aggregating the normalized and weighted values to obtain the final map, it was used the weighted linear combination. The results shows that the study area has strong impediment of 5,68% and very strong of 4,04% of the total area of the whatershed, while most of the land is suitable for mechanization, with null and slight impediment of 34,91 % and 27,02% respectively. In spatial terms, the criteria which conditioned more restrictions to mechanization were depth, stoniness and slope, checking little influence of the drainage and no influence of the texture. However, the slope weighing of 0,483 was the criterion that in terms of importance, most influenced the final result, allowing a marked compensation in the standings compared with the other criteria
Keywords: Zoneamento; Manejo do solo; Mecanização agrícola; Geoprocessamento; Zoning; Soil management; Agricultural mechanization; Geoprocessing; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO